Islamic Education Progresses in Muhammadiyah's Perspective: Strategies to Create A True Islamic Society - Intan Aulia Usmahwati; Nurul Latifatul Inayati (Universitas Muhammadiyah Surakarta, 2025)
Progressive Islamic Education is one of Muhammadiyah's ideas that is oriented towards the renewal of Islamic education to answer the challenges of changing times without abandoning Islamic values. The research aims to analyze advanced Islamic education from the perspective of Muhammadiyah and formulate educational strategies in realizing a true Islamic society. This research uses a qualitative research method with a type of library research . His approach uses a hermeneutic approach to interpret progressive Islamic education from the perspective of Muhammadiyah and the strategy of Islamic Education in creating a true Islamic society. The data collection technique is taken from primary sources and secondary sources. The primary source uses a book entitled Paradigm of Progressive Education by Dr. Mohammad Ali, M. Pd (2017). As well as secondary sources from a journal entitled Development of Progressive Islamic Education from the Perspective of Muhammadiyah by Ismunandar (2021). This research uses data analysis techniques obtained through data discovery, data reduction, data presentation, and conclusion drawn. The results of the study show that progressive Islamic education is understood as an integrative effort that combines Islamic values, science, and modern education systems to form Islamic people and society which truly includes the integration of Islam and knowledge, strengthening the orientation of education that is adaptive to changing times, the use of digital technology, multidisciplinary and collaborative approaches, leadership transformation and governance of educational institutions Islam, strengthening character and human values and the role of parents in reminding them of the motivation to learn religion in children. This research is expected to contribute to the development of progressive Islamic Education thinking as a long-term social transformation strategy.